Modern banking law - E.P. Ellinger (Oxford University Press, 2002)
This book sets banking law against the background of general legal doctrines, discussing its operation in the context of its wider economic function. It examines the broad spectrum of banking organizations in the UK, the new regulatory regime of the Financial Services and Markets Act, banker and customer relationships, and the different types of loan and credit agreements in operation